A review of Fiqh Siyasah Tanfidziyyah on the implementation of the mayor regulation on civil servant discipline at the Inspectorate of Bandar Lampung City - Alfina Damar Wulan; Frenki Frenki; Muhammad Jayus (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
This study aimed to analyze the implementation of working hour discipline enforcement for Civil Servant (PNS) based on Article 4 letter (f) of the Mayor of Bandar Lampung Regulation Number 25 of 2021 at the Bandar Lampung City Inspectorate through the perspective of Fiqih Siyasah Tanfidziyyah. The research method used was qualitative field research with a descriptive-analytical approach. Primary data were collected through in-depth interviews with relevant authorities at the Inspectorate, while secondary data were obtained through documentation studies and legal literature. The data analysis technique employed an interactive model comprising data reduction, data display, and conclusion drawing. The results showed that the enforcement of discipline at the Bandar Lampung City Inspectorate ran effectively by utilizing the